Analisis Kualitas Pelayanan Publik Berdasarkan Kajian Indeks Kepuasan Masyarakat (IKM) Pada Layanan Repositori Institusi - Beta Ria Febrianti; Novita Olivien; Winta Efrinalia (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
The problem studied in this study is the Community Satisfaction Index for service units of government agencies in the Regulation of the Minister of State for Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 at the UPT Library of Sriwijaya University. The purpose of this study was to determine the Community Satisfaction Index in library services, especially the Sriwijaya University institutional repository service. The method used in this research is descriptive quantitative. The research subjects were users of Sriwijaya University institutional repository services as many as 98 respondents obtained using the slovin formula. The sampling technique used is accidental sampling. Respondents were selected randomly according to service coverage. Data collection techniques using questionnaires and observation. The results of the study using the community satisfaction index method, especially in institutional repository services at the Sriwijaya University Library UPT, found that institutional repository services were considered very good. The results showed that the Community Satisfaction Index for institutional repository services at the Sriwijaya University Library UPT was 89.88 so that the quality of service was A.